The Islamic Kingdom of India: The Mughal Dynasty and the End of Its Power - Risdawati, Risdawati; Rusli, Nor Muhammad; Nurdiasnyah, Ahmad Farul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The Islamic civilization of the Mughal dynasty, which ruled India from the 16th century to the mid-19th century, was one of the most influential Islamic dynasties in the history of South Asia. This study focuses on tracing the major achievements of the dynasty in the fields of architecture, art, science, governance systems, and the integration of local culture, as well as identifying the factors that led to the fall of Mughal power in India. The research method used is library research, including historical books, journal articles, manuscripts, and related documents, analyzed through content analysis.Mughal rulers such as Akbar, Jahangir, Shah Jahan, and Aurangzeb played significant roles in shaping a unique and grand Indo-Islamic cultural synthesis, with monumental legacies such as the Taj Mahal, a merit-based bureaucratic system, and relative religious tolerance. However, by the 18th century, the Mughal dynasty began to decline due to internal conflicts, bureaucratic corruption, and pressure from British colonial powers. The fall of Mughal rule marked the end of the classical Islamic civilization era in India, though its legacy continues to live on in the social, cultural, and historical fabric of the Indian nation to this day.